Elevated Bone Hardness Under Denosumab Treatment, With Persisting Lower Osteocyte Viability During Discontinuation - Jähn-Rickert, Katharina; Wölfel, Eva M.; Jobke, Björn; Riedel, Christoph; Hellmich, Maya; Werner, Mathias; McDonald, Michelle M.; Busse, Björn (Frontiers in Endocrinology, 2020)
Denosumab is a potent osteoclast inhibitor targeted to prevent osteoporotic bone loss and thereby reduce fractures in the aging population. Recently an elevated risk of rebound fractures following denosumab discontinuation was identified, unless patients were transitioned to an alternative anti-resorptive medication. How denosumab affects the interaction of mechanosensitive osteocytes and bone quality remains unknown. We hypothesized that denosumab influences osteocyte function contributing to bone reorganization and increased fractures during discontinuation. Bone quality and osteocytes were assessed in archived iliac crest bone biopsies obtained from patients with high fracture occurrence from 2011-2016. Biopsies were obtained due to high fracture occurrence prior and during osteoporosis therapy from i) patients with at least two semi-annual subcutaneous injections of 60 mg denosumab, ii) patients with rebound fractures during discontinuation, and iii) patients of a treatment-naive group. In total, biopsies from 43 individuals were analyzed (mean age 65.5±12.1 yrs). Our results showed that during denosumab treatment iliac cortical bone had a higher bone tissue hardness compared to treatment-naive bone (p=0.0077) and a higher percentage of mineralized osteocyte lacunae (p=0.0095). The density of empty osteocyte lacunae was higher with denosumab compared to naive (p=0.014) and remained high in trabecular bone during discontinuation (p=0.0071). We conclude that during denosumab treatment increased bone hardness may contribute to improved fracture resistance. In biopsies from patients with high fracture occurrence, denosumab treatment reduced osteocyte viability, an effect which persisted during treatment discontinuation. High-resolution imaging of osteocyte viability indicates a role for osteocytes as a potential future mechanistic target to understand rebound bone loss and increased fractures with denosumab discontinuation.